Lanscape Changes on the Polish Coastline Related to Tourism Development - Gerstmannowa, Elżbieta (Turyzm/Tourism, 2005)
The 15-year long period of socio-economic transformation in Poland has seen a dramatic development in coastal tourism. This paper, based on investigations conducted between 1989 and 2004, analyses tourism-related changes in Poland’s coastal regions. It discusses their main economic functions, the phases of tourism development and trends in landscape change.